PERANAN CAHAYA PEREMPUAN WOMEN’S CRISIS CENTRE (WCC) BENGKULU DALAM MENANGANI KASUS KDRT PERSPEKTIF HUKUM ISLAM DAN UU NO. 23 TAHUN 2004 TENTANG PENGHAPUSAN KDRT - Eli Rahmidiani (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
The purpose of this study is to find out how the role of women’s women’s crisis center Bengkulu in handling cases of domestic violence in the perspective of Islamic Law and  Law Number twenty  three Year two four About Aboli- tion of Domestic Violence. This type of research is field research (field research) supported by library  research (library research). From  the  result  of this research, it is concluded that  the  role of women’s crisis center Bengkulu women in handling cases  of domestic violence in collaboration with legal aid institutions, medical, police,  and  courts, this  co- operation is called  case-handling network in an effort to reach cases  of domestic violence and  sexual  violence can be handled and  facilitated by victims  such  as safe houses, counseling rooms, to share stories and  facilities  in the form of legal assistance and handling in a familial manner while reducing the number of sexual violence handled by prevention programs. Analysis of Islamic law against domestic violence that in Al-Qur’an Surah  An-Nisa ‘verse thirty-four explains that a husband should not immediately hurt  his wife with a painful blow. Since Islam does not teach such a thing, there have been good and  right rules when the husband is facing such  problems. Although beating the wife is justified in Is- lam, it is hitting that does not hurt the wife and with educational intentions. Analysis of Law Number Twenty-three Years Two Thousand Four  About Abolition of Domestic Violence  is able  to avoid  family violence, when disharmony occurs between husband and wife. More broadly, it is necessary to have fundamental changes in women’s status and attitudes toward both women and men  in society,  the need for continuous and strategic efforts to deconstruct traditional power structures that have been considered legitimate and deconstruct cultural assumptions and religions that strengthen and legitimize violence